Petroleum and global tectonics - Fischer, Alfred George 1920-2017; Judson, Sheldon 1918-1999 (Princeton University Press, 2017)
The recent prominence of global tectonics has been as spectacular as it has been promissory of ramifications throughout established geological thought. The academic concepts of tectonics --continental drift, sea-floor spread, the definition of the major tectonic plates of the world, to cite only a few--are now regarded as essentially valid. Suggesting, as they do, a re-examination of many geological tenets, one may ask what bearing tectonics have on the formation and accumulation of petroleum. This volume addresses that question and presents the implications of the theoretical advances on the essential quest for petroleum and its by-products.Originally published in 1975.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905
Im Vorwort: "The papers of this volume were presented at the 109th meeting of the Princeton University Conference held in Princeton on March 10 and 11, 1972."
Keywords: Geologie; Petroleum -- Geology -- Congresses; Plate tectonics -- Congresses; Tektonik; Erdöllagerstätte; Konferenzschrift